Age-Related Effects on Memory for Social Stimuli: The Role of Valence, Arousal, and Emotional Responses - Hess, Thomas M. (Exp Aging Res, 2017)
BACKGROUND: Previous research (Hess, Popham, Dennis, & Emery, 2013) suggested that age-based positivity effects in memory were attenuated with social stimuli. We examined the degree to which this generalized across arousal levels associated with social images. We also examined variations in approach and avoidance responses to images, and how these were differentially related to memory in younger versus older adults. METHODS: In Experiment 1, young (22 – 43 years) and older (65 – 85 years) adults recalled positive and negative social scenes that were high or low in arousal. In Experiment 2, young (20 – 40 years) and older (65 – 83 years) adults viewed and recalled the same scenes under instructions designed to alter arousal, and approach and avoidance ratings for each image were recorded. RESULTS: In Experiment 1, age differences in recall were confined to high-arousal, negative images, with young adults exhibiting superior memory relative to older adults. There was no evidence of an age-related positivity effect for low arousal social scenes. This result was replicated in Experiment 2, but distancing instructions minimized the age difference in recall for high-arousal, negative images. Approach and avoidance ratings differentially predicted recall across age groups, with stronger associations in the young. CONCLUSION: The results are consistent with emerging evidence demonstrating that valence-based biases associated with aging (e.g., positivity effect) are specific to the context and stimulus characteristics. Differences in prediction of recall responses from approach and avoidance ratings across age groups suggested that the observed effects in memory reflected differences in responses to the characteristics of stimuli.